First faunistic study of Diplura in north of Iran with records of two species of Campodea (Campodeidae) - Azadbakhsh, Saeed; Nozari, Jamasb (Entomologica Fennica, 2016)
The hexapod fauna of Iran is still very incompletely known. The current study is the first report of dipluran species from Iran. Our studies and sampling were done in two northern provinces Mazandaran and Alburz during March to August 2012. Forty-five specimens of this order were collected. All the specimens were identified as Campodea (Dicampa) sprovierii Silvestri, 1932 or Campodea (Campodea) fragilis Meinert, 1865 (Campodeidae). Both the species are reported from Iran for the first time.